ANATOMICAL STUDIES OF THE FRUIT OF ZIZIPHUS RUGOSA - PREMA G; CHITRA M (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to study the anatomical features of the fruit Ziziphus rugosa. Methods: Surface view, longitudinal, transverse section (T.S), and powder microscopy of the fruits were studied. Results: The fruit is a drupe and shows vertical, irregular brown markings on the surface. The surface of the seed has irregular reticulate thick marking of brown. The longitudinal sections (L.S) of the fruit show thin green epicarp, wide soft mesocarp, and dark brown thick endocarp. In longitudinal view, the seed shows a thick conical part, thick wide shell which is hard. In the cotyledon is more or less cordate,white and soft with shallow notch at the upper end. In T.S, the fruit appears circular with soft pericarp, thick dark brown seed coat of sclereids, and vertically elongated white cotyledon. The epicarp layer is broken at certain places. In the mesocarp, some of the cells have dense tannin content and others have mucilage substance. The mucilaginous canals are wide, unbranched, and wavy. Some of the mesocarp cells contain dense accumulation of protein bodies. The sclerotesta contains palisade or macrosclereids. The seed consists of two elliptical, flat cotyledons which show dense accumulation of starch grains and small less prominent vascular strand. The powder microscopy of the fruit contains abundant dark mucilaginous substance. Fragments of epidermal cells of the pericarp and mesocarp cells are frequently seen. The seed coat epidermal cells are polyhedral with lignified cell walls. The circular brachy sclereids were often seen in the mesophyll tissue of the fruit. The ground parenchyma with various shapes and size is also noticed. Conclusion: This study revealed the presence of mucilaginous substance, tannin, sclereids, starch grains, and protein bodies. Therefore, this material will be efficient for eliminating some nutritional deficiency diseases.